Linaclotide increases cecal pH, accelerates colonic transit, and increases colonic motility in irritable bowel syndrome with constipation. Issue 2 (23rd October 2018) - Farmer, Adam D.; Ruffle, James K.; Hobson, Anthony R.
Abstract: Background: Linaclotide is efficacious in the management of irritable bowel syndrome with constipation (IBS‐C), yet relatively little is known regarding its effect on human gastrointestinal physiology. The primary aim of the study was to examine the effect of linaclotide on change in pH across the ileocecal junction (ICJ), a proposed measure of cecal fermentation, and its relationship to symptoms and quality of life (QoL) in IBS‐C. Methods: A total of 13 participants with Rome III IBS‐C underwent a standardized wireless motility capsule (WMC). Stool consistency was measured using the Bristol stool form scale (BSFS) and frequency with spontaneous bowel movements (SBM). Gastrointestinal symptoms and QoL were assessed using validated questionnaires. The WMC and questionnaires were repeated after 28 days of linaclotide 290 g po od. Key Results: Linaclotide reduced the change in pH across the ICJ (−2.4 ± 0.2 vs −2.1 ± 0.4, P  = 0.01) as a function of a relative alkalinization of the cecum (5.2 ± 0.2 vs 5.5 ± 0.3, P  = 0.02 ) . Linaclotide accelerated colonic transit time (2650 minutes (2171‐4038) vs. 1757 (112‐3011), P  = 0.02), increased colonic log motility index (15 ± 1.8 vs. 16.5 ± 1.8, P  = 0.004) but had no effect of gastric emptying or small bowel transit. Change in pH across the ICJ correlated with improvement in symptom intensity, unpleasantness, and visceral sensitivity index ( r  = 0.62, P  = 0.03, r  = 0.63, P  = 0.02, r  = 0.62, P  = 0.02) and with increases in BSFS type and SBM ( r  = 0.9, P  < 0.0001, r  = 0.6, P  = 0.02). Conclusions & Inferences: Linaclotide's effects are confined to the colon where it increases cecal pH, potentially representing a reduction in cecal fermentation and accelerates colonic motility. Abstract : Linaclotide has established efficacy in managing IBS with constipation. Little is known about its effects on GI physiology. Herein, we demonstrate that linaclotide reduces caecal pH and its motility effects are confined to the colon.